2020
DOI: 10.1016/j.molp.2020.02.011
|View full text |Cite|
|
Sign up to set email alerts
|

HY5-HDA9 Module Transcriptionally Regulates Plant Autophagy in Response to Light-to-Dark Conversion and Nitrogen Starvation

Abstract: Light is arguably one of the most important environmental factors that determines virtually all aspects of plant growth and development, but the molecular link between light signaling and the autophagy pathway has not been elucidated in plants. In this study, we demonstrate that autophagy is activated during light-todark conversion though transcriptional upregulation of autophagy-related genes (ATGs). We showed that depletion of the ELONGATED HYPOCOTYL 5 (HY5), a key component of light signaling, leads to enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 75 publications
4
80
0
Order By: Relevance
“…Cytosolic materials can be encapsulated and delivered to the vacuole/lysosome via the macroautophagy (hereafter referred to as autophagy) pathway. In macroautophagy, a double membrane-bound structure termed the autophagosome forms, which engulfs cargo proteins or organelles for subsequent delivery to the vacuolar lumen for proteolysis, or induces hydrolysis upon fusion between the autophagosome and vacuole/lysosome (Li and Vierstra 2012;Marshall and Vierstra 2018;Zhuang et al 2018;Yang et al 2020aYang et al , 2020b. Besides the autophagy pathway, another system that recognizes and delivers ubiquitinated cargo to the vacuole is the multivesicular body (MVB)-mediated endosomal sorting pathway, which is regulated by the endosomal sorting complex required for transport (ESCRT) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Cytosolic materials can be encapsulated and delivered to the vacuole/lysosome via the macroautophagy (hereafter referred to as autophagy) pathway. In macroautophagy, a double membrane-bound structure termed the autophagosome forms, which engulfs cargo proteins or organelles for subsequent delivery to the vacuolar lumen for proteolysis, or induces hydrolysis upon fusion between the autophagosome and vacuole/lysosome (Li and Vierstra 2012;Marshall and Vierstra 2018;Zhuang et al 2018;Yang et al 2020aYang et al , 2020b. Besides the autophagy pathway, another system that recognizes and delivers ubiquitinated cargo to the vacuole is the multivesicular body (MVB)-mediated endosomal sorting pathway, which is regulated by the endosomal sorting complex required for transport (ESCRT) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, afr1 and afr2 mutants exhibit elongated petioles and an open rosette structure, which is in contrast to the stunted hda9 mutant phenotype ( Gu et al , 2013 ), whereas similarly to hda9 and pwr , the afr mutants exhibit early flowering ( Gu et al , 2013 ). Additional proteins shown to interact with HDA9 include ASG2 ( Ducos et al , 2017 ), EARLY FLOWERING3 (ELF3), and possibly LUX ARRHYTHMO (LUX) ( Lee et al , 2019 ; Park et al , 2019 ), VP1/ABI3-LIKE 1 (VAL1) and VAL2 ( Zeng et al , 2020 ), ELONGATED HYPOCOTYL 5 (HY5) ( Yang et al , 2020 ), and ABA INSENSITIVE4 (ABI4) and ABI3 ( Baek et al , 2020 , Khan et al , 2020 ). These interactions are discussed below ( Fig.…”
Section: Hda9-interacting Proteins; the Hda9–hos15–pwr Core Hdac Compmentioning
confidence: 99%
“…The transcription factors WRKY53 ( Chen et al , 2016 ; Zheng et al , 2020 ), ABI4, ABI3 ( Baek et al , 2020 , Khan et al , 2020 ), and HY5 ( Yang et al , 2020 ), the epigenome readers VP1/ABI3-LIKE 1 (VAL1) and VAL2 ( Zeng et al , 2020 ), the circadian clock Evening Complex (EC) transcription factor(s) ELF3 and possibly LUX ( Lee et al , 2019 ; Park et al , 2019 ), and AT-hook motif-containing protein AHL22 ( Yun et al , 2012 ) are currently the only confirmed HDA9-interacting proteins with DNA binding capacity ( Fig. 1 ).…”
Section: Hda9-interacting Proteins; the Hda9–hos15–pwr Core Hdac Compmentioning
confidence: 99%
See 2 more Smart Citations